2009
DOI: 10.1152/japplphysiol.01133.2007
|View full text |Cite
|
Sign up to set email alerts
|

The difference in ventilation heterogeneity between asthmatic and healthy subjects quantified using hyperpolarized 3He MRI

Abstract: In this pilot study, algorithms for quantitatively evaluating the distribution and heterogeneity of human ventilation imaged with hyperpolarized (HP) (3)He MRI were developed for the goal of examining structure-function relationships within the asthmatic lung. Ten asthmatic and six healthy human subjects were imaged with HP (3)He MRI before bronchial challenge (pre-MCh), after bronchial challenge (post-MCh), and after a series of deep inspirations (post-DI) following challenge. The acquired images were rigidly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
145
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(149 citation statements)
references
References 46 publications
4
145
0
Order By: Relevance
“…In accordance to the computational models discussed above, this is indicative of a heterogenous pattern of constriction that includes randomly distributed airway closures or near closures (138). These observations are supported by ventilation imaging studies such as hyperpolarized 3 He MRI (39,207,234), single-photon emission computed tomography (116) and positron emission tomography (169). These studies showed that asthmatics have increased ventilation heterogeneity at baseline and, even if heterogeneous airway response to a spamogen is also observed in non-asthmatics, the level of ventilation heterogeneity achieved is greater in asthmatics (39,207,234).…”
Section: Non-uniform Ventilation With Air Trapping and Ahrsupporting
confidence: 73%
“…In accordance to the computational models discussed above, this is indicative of a heterogenous pattern of constriction that includes randomly distributed airway closures or near closures (138). These observations are supported by ventilation imaging studies such as hyperpolarized 3 He MRI (39,207,234), single-photon emission computed tomography (116) and positron emission tomography (169). These studies showed that asthmatics have increased ventilation heterogeneity at baseline and, even if heterogeneous airway response to a spamogen is also observed in non-asthmatics, the level of ventilation heterogeneity achieved is greater in asthmatics (39,207,234).…”
Section: Non-uniform Ventilation With Air Trapping and Ahrsupporting
confidence: 73%
“…The forced expiratory volume in the first second of expiration (FEV 1 ) and the forced vital capacity (FVC) were measured on the days of both the pretreatment and posttreatment MRI scans. In addition, we created color-coded maps that represented fractional ventilation per pixel normalized to the trachea signal, which is the maximum value, as per the methodologies described in Tzeng et al (25).…”
Section: Methodsmentioning
confidence: 99%
“…5), and COPD (van Beek et al, 2004). Patients with asthma demonstrated ventilation defects both before and after a challenge with methacholine or exercise (Samee et al, 2003;Tzeng et al, 2009), and a significant overlap of 3 He defects and hyperlucency on HRCT was found (Fain et al, 2008). In patients with COPD, primarily 3 He diffusion MRI has been applied to examine alveolar air space size as mentioned previously (see Emphysema).…”
Section: Imaging In Respiratory Diseases: From Animal Models To Patientsmentioning
confidence: 99%